Strength model of a cemented body based on self-compacting characteristics of tailings - Jun, Wang; Tian-Yu, Yang; Deng-Pan, Qiao; Jie, Chen; Zheng-Liang, Luo (Frontiers in Earth Science, 2023)
To investigate the strength and mechanical properties of self-compacting tailings, the direct shear test of tailings under different consolidation states and different water contents were carried out. The influence of consolidation stress and water content on the cohesion as well as internal friction angle of tailings were discussed. The cohesion and internal friction angle of unsaturated tailings increased firstly then decreased with the increasing of water content, the cohesion, and internal friction angle of tailings reached at the maximum when the water content was around 14%. The improvement of cohesion and internal friction angle of unsaturated tailings were presented with the increase of consolidation stress, which led to be stable when the consolidation stress had better performance than 1MPa; Combined with the Coulomb shear strength formula and the tailings self-weight compaction model, the expressions of the active pressure and passive pressure of tailings were attained at any height on the lateral restraint. The three-dimensional mechanical equilibrium of the cemented body was established by the limited equilibrium method. The three-dimensional strength analytical model of cementation in step Ⅰ was modified, and the strength model of cementation in stage open stoping with subsequent filling was constructed. This study provided technical supports and theoretical reference for the strength design of the one-step cemented backfill, the design and erection of the backfill retaining wall.